PENGARUH DEFATTING, FREKUENSI PENCUCIAN DAN JENIS DRYOPROTECTANT TERHADAP MUTU TEPUNG SURIMI IKAN LELE KERING BEKU [Effect of Defatting, Washing Cycle and Dryoprotectant Type on the Quality of Freeze Dried Catfish Surimi Powder] - Wahyu Ramadhan; Joko Santoso; Wini Trilaksani (Jurnal Teknologi dan Industri Pangan, 2014)
PENGARUH DEFATTING, FREKUENSI PENCUCIAN DAN JENIS DRYOPROTECTANT TERHADAP MUTU TEPUNG SURIMI IKAN LELE KERING BEKU[Effect of Defatting, Washing Cycle and Dryoprotectant Type on the Quality of Freeze Dried Catfish Surimi Powder]Wahyu Ramadhan*, Joko Santoso dan Wini Trilaksani Departemen Teknologi Hasil Perairan, Fakultas Perikanan dan Ilmu Kelautan, Institut Pertanian Bogor, Bogor Diterima 05 Agustus 2013 / Disetujui 08 April 2014ABSTRACT  Freeze dried surimi powder is a surimi type processed by freeze drying. To utilize oversized catfish and to reduce surimi handling cost, oversized catfish has been used as raw material of surimi powder. The study aimed to determine the effect of defatting (NaHCO3 concentration and soaking duration), washingcycle,and dryoprotectant type on catfish surimi, as well as quality differences between surimi powder and wet surimi. With regard to defatting step, soaking in NaHCO3 0.75% for 10 minutes was found as the best treatment and resulting in a fat content of 1.52%. Moreover, one time of washing cycle was found as the most appropriate procedure to obtain a superior quality of surimi with whiteness value 57.21%, water holding capacity 73.28%, salts soluble protein 7.17%, pH 6.69, and gel strength 482.3 g/cm2, folding value of 4.84, and teeth cutting value of 8.26. Trehalose 6% was the most suitable dryoprotectant resulting in surimi powder with water holding capacity of 8.01 mL/g, gel strength 826.3 g/cm2, salt soluble protein 18.98%, density 4.06 mL/10 g, rehydration capacity 3.81, emulsion capacity 69.3%, emulsion stability 59.3%, foaming capacity 25.33% and foaming stability 9.40%. The microstructure profile of surimi powder added with trehalose had more compact tissues, without any damage and clots, than that treated with other dryoprotectants. However, surimi powder still had lower protein content than wet surimi, and lower physical and chemical properties, particularly in its teeth cutting and folding characteristics.